Desenvolvimento de um método por ponto nuvem dos hormônios naturais E1 e E2 em amostras de urina e determinação por CLAE/EC utilizando eletrodo de diamante dopado com boro - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Cloud point extraction method (CPE) was used for the determination of estrone (E1) and 17β-estradiol (E2) hormones in human urine. The combination of the electrochemical detection techniques with high-performance liquid chromatography (HPLC-EC) was used for the detection and quantification of these hormones. A boron doped diamond electrode (BDD) pretreated cathodically was used as electrode material for all electrochemical measurements. The optimized chromatographic parameters resulted in a mobile phase composition of KH2PO4 (0.01 mol L-1; pH 5.0) / ACN (72:28 V/V), flow 1.2 ml min-1. An applied potential for electrochemical detection of 1.0 V x Ag/AgCl (3.0 mol L-1) was selected from hydrodynamic voltammograms constructed for each hormone changing the potential between 0.3 V and 1.2 V x Ag/AgCl (3.0 mol L-1). Limits of detection (S/N = 3) of 500 ng mL-1 and limits of quantification of 800 ng mL-1 were obtained for both E1 and E2 hormones without any extraction process. Urine samples at pH 5.0 and 7.0 were investigated aiming the influence of pH on the efficiency of the CPE process, and the optimum results for the most current signal of the hormones was obtained at pH 7.0. Extractor solvent volumes were changed in the 0.5-2.5 mL range, and the optimum results were obtained when using 1.0 mL of Tergitol TMN-6 surfactant (10% aqueous solution). From the equation of the calibration curves obtained with and without the CPE procedure it was possible to determine the pre-concentration factor (FC) and all the other parameters involving the efficiency of CPE method. A comparison of the efficiency of CPE method with direct liquid-liquid extraction with the organic solvent CCl4 was carried out and the results showed that the CPE method was quite superior to liquid-liquid extraction. The validation of the method was carried out from intra-day recovery experiments and inter-day and evaluated the accuracy, precision and repeatability. The proposed method was applied to individual samples of urine of 1 man, 1 pregnant woman, 1 woman in fertile age, and 1woman in lactating stage. The values of the variation coefficients of the recovery percentages were lower than 15%.
Development of a cloud point method of E1 and E2 natural hormones from urine samples and determination by HPLC/EC using boron doped diamond
Keywords: Extração por ponto nuvem; Eletrodo de diamante dopado com boro; Detecção eletroquímica; Hormônios estrogênios e urina; Cloud point extraction; Boron doped diamond electrode; Electrochemical detection; Estrogen hormones and urine; CIENCIAS EXATAS E DA TERRA::QUIMICA